Analisis Pemanfaatan Energi Panas pada Pengeringan Bawang Merah (Allium ascalonicum L.) dengan menggunakan Alat Pengering Efek Rumah Kaca (ERK): Analysis of Heat Energy Utilizationin Onion (Allium ascalonicum, L.)DryingusingGreenHouses Gasses(GHG)Drye - Zamharir Zamharir; Sukmawaty Sukmawaty; Asih Priyati (Jurnal Ilmiah Rekayasa Pertanian dan Biosistem, 2016)
Onion (Allium ascalonicum, L.) is one horticulture commodity that is widely cultivated by Indonesian society. There are many benefits that can be drawn from the onion and high economic value of these vegetables make farmers in various regions interested to cultivate them to earn huge profits. Purpose of this study was to analyze the needs of heat energy in the drying process of onions. Method used in this research was experimental methods by using Greenhouse Gasses (GHG) dryer for drying onion. This dryer utilizes solar energy as the only source of heat to raise temperature of the material in the drying process. On the first experimental stage (without materials) the highest temperature inside the dryer was 52°C and the lowest was 27°C, while the maximum temperature in the environment was 34°C and the minimum was 25°C. The average temperature difference between the dryer and the environment was 14°C with average solar radiation of 445 W/m². On the experiment using materials, the average temperature of the dryer during 4 days, the lowest was 37.75°C and the highest was 51.75° C; whereas the lowest and the highest environment temperature respectively was 25.8°C and 37.0°C. The average light intensity was 545 W/m², with average total amount of solar energy received was 2,227,262.7 kJ and the average drying efficiency was 39.9%.